Project planning, analysis and evaluation : theory and practice - Ndebbio, John E. Udo (Calabar, Nigeria: University of Calabar Press, 2007)
The book discusses project planning, analysis and evaluation. Topics covered includes project monitoring and evaluation; capital investment; distinction between public and private projects; cost benefit study; time value of money, comppounding and discounting; project cycle; project feasibility; evaluation techniques in appraising projects; capital budgeting; present value and investment ranking; shadow pricing; financial and economic analysis of a project.
Includes bibliographical references and index.
lje 04/09/2013
Loans
Keywords: Project planning; Project management; Project evaluation; Project analysis